The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.seizure.2017.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Eslicarbazepine acetate as a therapeutic option in a patient with carbamazepine-induced rash and HLA-A*31:01

Abstract: Eslicarbazepine acetate (ESL) is an anticonvulsant drug approved for the treatment of focal epilepsies, and related to oxcarbazepine and carbamazepine (CBZ), which are also derivatives of the dibenzazepine family. ESL is contraindicated in patients with hypersensitivity reactions to CBZ.We report a patient with frontal lobe epilepsy responding to treatment with ESL without any serious adverse effects after developing a severe skin rash following treatment with CBZ. HLA testing revealed an HLA-A*31:01 haplotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Of note is one patient who developed an allergic reaction with hypotension upon first infusion of BRV, and one adolescent (16 years) who developed a hyperpigmentation of both upper limbs following treatment with BRV for >6 months. In another patient, skin rash was probably due to carbamazepine exposure in the presence of a HLA‐A*31:01 haplotype . We observed two pregnancies, with exposure to BRV of 2 days in one case and approximately 6 weeks in a second case, during the first term.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Of note is one patient who developed an allergic reaction with hypotension upon first infusion of BRV, and one adolescent (16 years) who developed a hyperpigmentation of both upper limbs following treatment with BRV for >6 months. In another patient, skin rash was probably due to carbamazepine exposure in the presence of a HLA‐A*31:01 haplotype . We observed two pregnancies, with exposure to BRV of 2 days in one case and approximately 6 weeks in a second case, during the first term.…”
Section: Resultsmentioning
confidence: 69%
“…In another patient, skin rash was probably due to carbamazepine exposure in the presence of a HLA-A*31:01 haplotype. 23 We observed two pregnancies, with exposure to BRV of 2 days in one case and approximately 6 weeks in a second case, during the first term. In both patients, BRV treatment was stopped and they were immediately switched to LEV.…”
Section: Treatment-emergent Adverse Effectsmentioning
confidence: 73%
“…184,185 Eslicarbazepine is contraindicated in patients with hypersensitivity reactions to CBZ (European Medicines Agency, London, UK), but some studies have suggested that severe skin reactions occur less frequently with eslicarbazepine compared to other anticonvulsants, leading to treatment discontinuation in only 0.1% of the cases. 186 As data are scarce and contradictory, [187][188][189] further studies are clearly needed before definitive conclusions may be drawn. Eslicarbazepine has been shown to interact selectively with the inactive state of VGSCs through altered slow inactivation, as opposed to the effects on fast inactivation associated with CBZ and OXC.…”
Section: Additional Pharmacological Perspectivesmentioning
confidence: 99%
“… 43 In this respect, the official summary of product characteristics contraindicates ESL in patients with hypersensitivity reactions to CBZ. 9 A recent report described the case of a patient with the HLA-A*31:01 haplotype who, after the development of a severe cutaneous reaction following CBZ administration, was successfully prescribed ESL without experiencing any adverse event, 44 and it suggested that ESL may be considered if the benefits are thought to exceed the risks. The safety of ESL in subjects with HLA-B*15:02 or HLA-A*31:01 haplotypes and a history of CBZ- or OXC-induced hypersensitivity reactions remain, however, to be fully addressed in larger studies before drawing definitive conclusions.…”
Section: Introductionmentioning
confidence: 99%